Neonatal adjustments in respiratory and pulse rates in tropical breeds of buck-kids and doelings - Buhari Habibu (SpringerOpen, 2021)
Abstract Background The transition to pulmonary respiration and the termination of foetal cardiovascular shunts is expected to commence immediately after birth. Subsequently, alveolar ventilation and tissue perfusion must be established, despite the challenge of extra-uterine environmental conditions, which could be quite demanding, even to the adult animals. The current study evaluated neonatal adjustment and diurnally induced changes in respiratory and pulse rates in kids of Red Sokoto, Sahel and West African Dwarf (WAD) goats in a tropical climate. Results Morning and afternoon respiratory rates started decreasing (P < 0.05) in the second week of birth. The pulse rate in the morning hours rose (P < 0.05) on Day 1 with no significant fluctuation subsequently, while the pattern in the afternoon hours showed a progressive decrease (P < 0.05) after birth. Apart from the day of birth, respiratory rate on other days increased significantly from morning to afternoon hours. The afternoon pulse rate was higher (P < 0.05) on the day of birth, but lower (P < 0.05) on Day 2 as compared to the morning values; and no diurnal difference was observed in subsequent days. The WAD goats had significantly higher respiratory and pulse rates than Red Sokoto and Sahel kids, especially in the afternoon hours. Similarly, the values were higher (P < 0.05) in doelings than buck-kids during the morning hours. The correlation between respiratory and pulse rates was positive (P < 0.05) and the strength of the association increased with age. Conclusion It was concluded that the afternoon rise in ambient temperature induced the establishment of a clear diurnal variation in respiratory rate 24 h postnatal, while the diurnal variation in pulse rate was weak and irregular. The tropical climate may be quite challenging to the attainment of physiological stability in respiratory and cardiovascular functions of neonatal goat kids, especially during the hot season.